Characterization of volatile compounds produced by Lactobacillus helveticus strains in a hard cheese model - Cuffia, Facundo (2018)
Starter cultures of Lactobacillus helveticus used in hard cooked cheeses play an important role in flavor development. In this work, we studied the capacity of three strains of L. helveticus, two autochthonous (Lh138 and Lh209) and one commercial (LhB02), to grow and to produce volatile compounds in a hard cheese extract. Bacterial counts, pH, profiles of organic acids, carbohydrates, and volatile compounds were analyzed during incubation of extracts for 14 days at 37 ℃. Lactobacilli populations were maintained at 106 CFU ml−1 for Lh138, while decreases of approx. 2 log orders were found for LhB02 and Lh209. Both Lh209 and LhB02 slightly increased the acetic acid content whereas mild increase in lactic acid was produced by Lh138. The patterns of volatiles were dependent on the strain which reflect their distinct enzymatic machineries: LhB02 and Lh209 produced a greater diversity of compounds, while Lh138 was the least producer strain. Extracts inoculated with LhB02 and Lh 209 were characterized by ketones, esters, alcohols, aldehydes, and acids, whereas in the extracts with Lh138 the main compounds belonged to aromatic, aldehydes, and ketones groups. Therefore, Lh209 and LhB02 could represent the best cheese starters to improve and intensify the flavor, and even a starter composed by combinations of LhB02 or Lh209 with Lh138 could also be a strategy to diversify cheese flavor.